2009 IEEE Wireless Communications and Networking Conference 2009
DOI: 10.1109/wcnc.2009.4917524
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Framework for Dynamic Spectrum Management in MultiCell OFDMA Networks Based on Reinforcement Learning

Abstract: Abstract-In this work the feasibility of Reinforcement Learning (RL) for Dynamic Spectrum Management (DSM) in the context of next generation multicell Orthogonal Frequency Division Multiple Access (OFDMA) networks is studied. An RL-based algorithm is proposed and it is shown that the proposed scheme is able to dynamically find spectrum assignments per cell depending on the spatial distribution of the users over the scenario. In addition the proposed scheme is compared with other fixed and dynamic spectrum stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The first term in (3) performs the gradient ascent of the reward signal as in the learning algorithm considered in [17]- [19]. Parameter α(t) > 0 is called the learning rate (for details regarding its update see [17]). r i (t) is the average reward obtained asr i (t) = βr i (t) + (1 − β)r i (t − 1), with 0 < β 1.…”
Section: A Single Rl Agentmentioning
confidence: 99%
See 2 more Smart Citations
“…The first term in (3) performs the gradient ascent of the reward signal as in the learning algorithm considered in [17]- [19]. Parameter α(t) > 0 is called the learning rate (for details regarding its update see [17]). r i (t) is the average reward obtained asr i (t) = βr i (t) + (1 − β)r i (t − 1), with 0 < β 1.…”
Section: A Single Rl Agentmentioning
confidence: 99%
“…Second, a novel model for practical implementation of the reward signal is given, extending and exploiting what was briefly described in [17]- [19]. Third, an exhaustive performance comparison with, fixed, hybrid, and other DSA strategies within the private commons scenario is given, showing remarkable improvements over the rest of strategies.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Also, a centralized version of the RL-DSA algorithm is simulated [8]. It is expected that this centralized strategy outperforms distributed RL-DSA thanks to its global vision of the spectrum assignment, but self-organized systems, and in particular the distributed RL-DSA presented here, aim at approximate centralized performance while scalability and autonomous capabilities are given to the system.…”
Section: A Case Study 1 Performance Comparisonmentioning
confidence: 99%
“…Hence, RL has been successfully applied to spectrum sensing [6] or spectrum sharing [7] procedures in Cognitive Radio (CR). Also, in our previous work, we showed that RL can be used to implement centralized dynamic spectrum assignment (DSA) strategies for primary cellular networks [8].…”
Section: Introductionmentioning
confidence: 99%